Aplikasi Metode Chaid dalam Menganalisis Kecendrungan Penelitian Skripsi Mahasiswa pada Program Studi Pendidikan Matematika - Erwina Azizah Hasibuan; Adek Nilasari Harahap (Edumatika : Jurnal Riset Pendidikan Matematika, 2019)
This study aims to identify, analyze and map the results of students’ research on mathematics education in 2015-2018. This research used the CHAID algorithm that consists of 3 steps ie merging, splitting and stopping steps. The results of this research were (1) In 2015-2018, 51,9% of the students’ research used the classroom action research and 48,1% else used the descriptive, the analysis and the experiment. (2) 14,1% of the students used media for teaching and learning and 3,7% of them did not. (3) 8,1% were individual research and 5,9% were a collaboration or team research. (4) While the level of school and subject taught in schools did not effect the trend of student research.